Comparison of Lamotrigine and Oxcarbazepine Monotherapy Among Chinese Adult Patients With Newly-Diagnosed Focal-Onset Epilepsy: A Prospective Observational Study - Chen, Yuncan; Wang, Qinyue; Xu, Ye; Wu, Dongyan; Xu, Lan; Zhu, Guoxing; Wu, Xunyi (Frontiers in Neurology, 2022)
Objective: We performed a prospective cohort study to compare the efficacy, safety, effect on mood and quality of life between lamotrigine (LTG) and oxcarbazepine (OXC) monotherapy among Chinese adult patients with newly-diagnosed focal-onset epilepsy (FOE). Methods: We enrolled 106 patients with new-onset FOE, with 56 in the OXC group and 50 in the LTG group. Efficacy was evaluated as seizure-free, effective and ineffective. We also assessed their mood state with the Zung Self-rating Scale for anxiety (Z-SAS) and Zung Self-rating Scale for Depression (Z-SDS) and quality of life (QOL) with Quality of Life in Epilepsy (QOLIE-31) at their baseline, 3-month and 6-month visit. Intra-group and inter-group comparisons were made. Correlation analysis and multiple regression analysis were also conducted. Results: The two groups were well matched in most of the characteristics. As for efficacy, 33 patients in the OXC group were evaluated as seizure-free and 15 as effective, while in the LTG group, 31 were seizure-free, and nine were effective. No significant differences could be observed between the two groups(P=0.429). Through multiple regression analysis, we found that OXC monotherapy was more likely to predict a seizure-free state (OR=1.76) than LTG, but the difference didn’t reach statistical significance (P=0.322) after correcting for other clinical variables. Both groups had adverse events such as fatigue, drowsiness, dizziness and rash, most of which were mild and transient. In the OXC group, SAS (P=0.067) and SDS (P=0.004) scores reduced at the 6-month visit, while the QOLIE-31 score significantly increased (P=0.001). While in the LTG group, a significant decrease of SAS and SDS scores and an increase of QOLIE-31 score could be witnessed (All P<0.001). The inter-group comparison showed that improvement of SAS and SDS in the LTG group was more evident than that in the OXC group. Correlational analysis indicated that the improvement of mood and life quality was independent of seizure frequency and treatment efficacy. Conclusions: OXC and LTG are effective as monotherapy and can be considered first-line selection among adult patients with new-onset FOE. Most adverse events are mild, transient and tolerable. The two drugs improve the patients' mood state and quality of life.